Cultural aspects of the formation of folk musical instruments in Ukraine (Pedagogy of Higher and Secondary Education, 2012)
Bilonenko H. O., Korolkov E. S. Cultural aspects of the becoming of folk musical instrument in Ukraine.Some cultural aspects of formation and development of folk musical instruments in Ukraine are revealed in the article. Historical peculiarities of forming instrumental mastery folk culture and profession music culture are shown.
Keywords: instruments; cultural; professional musicians